2014
DOI: 10.1002/fut.21698
|View full text |Cite
|
Sign up to set email alerts
|

Investor Beliefs and the Demand Pressure on Index Options in Taiwan

Abstract: The effects of demand pressure on option prices have already been well documented within the extant literature; however, little appears to be known with regard to where the demand pressure on options originates. We set out in the present study to examine the ways in which investor beliefs affect the demand pressure on TAIEX options, employing forward‐looking risk‐neutral index distributions to evaluate such beliefs. Our examination of 2005–2012 high‐frequency data reveals that with an increase in the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Further, Bollen and Whaley (2004) do not clearly interpret the information effect of options demand but rather explain only the mechanical relationship between investor demand and changes in the implied volatility structure. Subsequent studies, such as those of Chan, Cheng, and Lung (2004), Chuang, Tsai, and Wu (2020), Duan and Hung (2010), Larkin, Brooksby, Lin, and Zurbruegg (2012), Pai, Lee, and Lin (2017), and Pan, Shiu, and Wu (2015), all of which employ Bollen and Whaley's (2004) net buying pressure measure, share the same limitation. They ignore the fact that each options market contains different types of options demand.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Bollen and Whaley (2004) do not clearly interpret the information effect of options demand but rather explain only the mechanical relationship between investor demand and changes in the implied volatility structure. Subsequent studies, such as those of Chan, Cheng, and Lung (2004), Chuang, Tsai, and Wu (2020), Duan and Hung (2010), Larkin, Brooksby, Lin, and Zurbruegg (2012), Pai, Lee, and Lin (2017), and Pan, Shiu, and Wu (2015), all of which employ Bollen and Whaley's (2004) net buying pressure measure, share the same limitation. They ignore the fact that each options market contains different types of options demand.…”
Section: Introductionmentioning
confidence: 99%
“…There is one‐to‐one correspondence between implied volatility and option prices: thus, in order to explore arbitrage opportunities as early as possible, the conventional method is to use implied volatility as the proxy for option prices. For our examination of implied volatilities in the two instruments, we employ the risk‐ neutral‐volatility approach proposed by Bakshi, Kapadia, and Madan (), while also following Pan et al () to exclude from the sample all options with prices of less than 0.3 points in order to avoid potential microstructure‐related bias: any options violating the arbitrage boundary were also removed from the sample.…”
Section: Resultsmentioning
confidence: 99%
“…If this inference is correct, then higher market uncertainty and pessimism should be discernible during the third week of each month, as compared to all other weeks. In order to measure investor belief about uncertainty and their pessimism with regard to the performance of the stock market, we follow the approach developed by Pan et al () to calculate risk‐neutral volatility and skewness on a 1‐min basis.…”
Section: Investor Sentimentmentioning
confidence: 99%
“…A number of studies have shown that investor sentiment, as a branch of behavioural finance theory (Bozionelos, 2006), can make the investment decision-making be influenced by their own internal subjective factor, which ultimately leads to systematic bias in investment decisions (Lux, 2011). Theorists define this subjective factor as investor sentiment (Pan, Shiu, & Wu, 2015). Therefore, the amplification mechanism of investors' positive feedback and negative feedback on future market changes will have a significant impact on the investment market (Cetin, 2014;Smimou, 2014).…”
Section: Introductionmentioning
confidence: 99%